Digital Transformation for Sustainability in Industry 4.0: Alleviating the Corporate Digital Divide and Enhancing Supply Chain Collaboration - Qi Li; Weijian Tian; Hua Zhang (Systems)
The swift advancement of digital technologies under Industry 4.0 has significantly transformed business operations and supply chain management. These advancements hold the potential to improve efficiency, reduce waste, and foster sustainable development; however, they also create challenges due to the uneven adoption of digital technologies across enterprises. (1) Background: The adoption of digital technologies across supply chains is uneven, resulting in a digital divide between enterprises. This disparity disrupts supply chain collaboration and alignment with sustainable practices. (2) Methods: This research examines how the corporate digital divide affects the supply–demand imbalance by employing a quantitative method to identify obstacles and strategies for improving collaboration. This research employs a quantitative approach, specifically multiple regression analysis, to investigate how the digital divide among enterprises affects the supply–demand imbalance and to identify strategies for overcoming collaboration barriers. The research utilizes firm-level data from the Chinese stock market and accounting research databases and performs robustness checks, including methods such as the instrumental variable approach and the Heckman two-stage model, to ensure the validity of the findings. (3) Results: The study finds that the corporate digital divide exacerbates imbalances in both upstream and downstream chains. Elevating supply chain resilience has effectively alleviated this relationship. Specifically, the strengthening of resource resilience and process resilience has effectively alleviated the impact of the corporate digital divide on the supply–demand imbalance in the upstream supply chain, while the enhancement of system resilience and product resilience has effectively mitigated the impact of the corporate digital divide on the supply–demand imbalance in the downstream supply chain. Heterogeneity analysis indicates that the impact of the digital divide in supply chain enterprises on supply–demand imbalance varies under different conditions of network centrality, supply chain concentration, government digital focus, and enterprise nature. (4) Conclusions: To foster sustainability in Industry 4.0, enterprises must bridge the corporate digital divide and enhance supply chain collaboration. It is recommended to mitigate upstream supply chain disruptions caused by the digital divide by improving resource and process resilience while alleviating downstream impacts through strengthened system and product resilience. Furthermore, fostering collaborative digital development among enterprises is essential for optimizing supply chain sustainability.